Analysis of Idiom Forms and Meanings in Legal and Criminal News in Analisa and Waspada Newspapers on March-April 2021 Edition - Wiana, Desri; Nst, Lily Maryam; Khairani, Ade Irma (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research is entitled “Analysis of Idiom Forms and Meanings in Legal and Criminal News in Analisa and Waspada Newspaper March-April 2021 Edition. The research model used is qualitative research. The data analysis technique used a qualitative descriptive method, which is a method that describes the data naturally and as it is. The results found that the number of idioms in the Analisa and Waspada newspaper March-April 2021 edition was 172 idioms. The dominant type of idiom was found in 110 or 63.9%. While some idioms are 62 or 36.0%. It can be concluded that some idioms are more often used in newspaper language sentences because the meanings that appear are not fully expressions, so that readers will more easily understand the contents of the news published in the two newspapers. The two newspapers studied have similarities in the delivery of legal and criminal news. However, the form of idioms used in sentences is more commonly found in the Analisa Newspaper than Waspada.